The Effect of the Traditional Lop-Lop Manok Game on Developing Social Interaction Skills in Early Childhood - Salsabilla, Putri; munawwarah (JURNAL PENA PAUD, 2026)
Social interaction skills are an important aspect of early childhood development, but in reality, there are still children who are unable to cooperate, communicate, and obey rules in group play activities. One effort that can be made to improve these skills is through the use of traditional games that are rich in social and cultural values. This study aims to determine the effect of the traditional game Lop-Lop Manok on the social interaction skills of early childhood at TKN 5 Banda Aceh. This study used a quantitative approach with a one-group pretest-posttest experimental design. The research subjects consisted of 18 children in group B. Data collection techniques were carried out through observation and documentation of children's social interaction skills before and after being given treatment in the form of applying the traditional game of Lop-Lop Manok. The data obtained were analyzed using a paired sample t-test. The results showed that the average score for children's social interaction skills increased from 2.13 in the pretest to 2.62 in the posttest. The t-test results showed a significance value of 0.000 (p < 0.05), meaning that there was a significant difference between children's social interaction skills before and after the treatment. It can be concluded that the traditional game of Lop-Lop Manok has a significant effect on improving the social interaction skills of early childhood at TKN 5 Banda Aceh, as well as being an effective learning medium that supports the preservation of local Acehnese culture. The characteristics of the traditional game of Lop-Lop Manok are that it is a game originating from Aceh, has simple rules, does not require special equipment, involves social interaction, has educational value, develops social-emotional aspects, supports motor development, and is enjoyable.